Effect of Different Mushrooms Fed to Eimeria-Challenged Broilers on Rearing Performance - Willis , W.L.; Wall, D.C.; Isikhuemhen, O.S.; Ibrahim, S.; Minor, R.C.; Jackson, J.; Hurley, S.L.; Anike, F. (International Journal of Poultry Science, 2012)
An experiment was conducted to evaluate the feeding of four mushrooms separate and combined via Fungus Myceliated Grain (FMG) on broiler chicken performance after an Eimeria challenge at 14 days of age. Male broilers (n-180) were randomly allocated to 1 of 12 treatments, replicated 3 times with 5 chicks each in a battery cage system for 28 days as follows: 1) Control-1 (no FMG, unchallenged), 2) Control-2 (no FMG, challenged), 3) Shiitake (S) 5% FMG, (unchallenged), 4) Shiitake (S) 5% FMG, (challenged), 5) Reishi (R) 5% FMG, (unchallenged), 6) Reishi (R) 5% FMG, (challenged), 7) Cordyceps (C) 5% FMG, (unchallenged), 8) Cordyceps (C) 5% FMG, (challenged), 9) Oyster (O) 5% FMG, (unchallenged), 10) Oyster (O) 5% FMG, (challenged), 11) S+R+C+O 5% FMG, (unchallenged) and 12) S+R+C+O 5% FMG, (challenged). Live weight and feed intake were measured at day 7, 14, 21, 28 and oocyst excretion, mortality and bursa weights at day 28. Coccidiosis infection induced depressed body weights in challenged birds at 21 and 28 days. Eimeria challenged birds in treatment four given Shiitake 5% FMG had body weights that were significantly higher than the other challenged birds at 21 days. The 28-day weight did not differ from each other in the challenged and unchallenged except for treatment seven (Cordyceps-unchallenged) which was significantly lower. While Eimeria counts at day 28 showed significant (p<0.05) differences amongst challenged groups, significant differences were not found in the unchallenged treatment groups. There were significant (p<0.05) differences in Eimeria counts and bursa weights between challenged and unchallenged birds at day 28. The results from this study demonstrate that Shiitake was superior and Cordyceps, at the 5% inclusion level, depressed body weight in birds whether they were challenged or unchallenged but data suggest that Cordyceps may reduce oocyst shedding.